Analisis Timbulan Sampah Domestik Di Kecamatan Siak Hulu Dan Kecamatan Tambang - Rikhatul A’ini; Jecky Asmura; Aryo Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Siak Hulu District and Tambang District are also buffer zones. Siak Hulu District consists of 12 villages / wards with an area of 987 km2 and a population of around 110,327 people. Meanwhile, Tambang District has 17 villages with an area of approximately 489.91 km2 and a population of around 95,627 people. The population growth rate of Siak Hulu Subdistrict is 3.02% and Tambang Subdistrict is 2.85%. The increase in population and changes in the consumption pattern of the community causes the volume of waste to increase, the increase in the amount of waste that is not accompanied by a proper handling system will cause solid waste problems that are difficult to solve. The calculation of waste generation carried out refers to SNI 19-3964-1995, the unit of large city waste generation = 2 - 2.5 L / person / day, or = 0.4 - 0.5 kg / person / day, the unit of small town waste generation = 1.5 - 2 L / person / day, or = 0.3 - 0.4 kg / person / day. Siak Hulu District produces 354,058 m3 / day of waste. And Tambang District produces 181,186 m3 / day of waste. Key words: Siak Hulu District and Tambang District, waste generation, domestic waste.